2013
DOI: 10.1111/tbed.12089
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Characterization of Peste des Petits Ruminants Viruses From Outbreaks Caused by Unrestricted Movements of Small Ruminants in Pakistan

Abstract: Peste des petits ruminants (PPR) is an endemic disease of small ruminants, and vaccination has been the method of control but outbreaks are continuously occurring in Pakistan. The following study presents a detailed investigation of an outbreak, suspected to be PPR, probably introduced by PPRV-infected sheep and goats from Sindh Province (north-west) to Punjab Province (central) of Pakistan during the flood relief campaign in 2011. A total of 70 serum samples from 28 different flocks were tested with competiti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 21 publications
0
17
2
Order By: Relevance
“…The reported prevalence of PPR in goats at present study was 1.37% and was in opposite with the results higher prevalence reported by Al-Dubaib (26) (13,(19)(20)(21)(22). Aunque puede no haber una variación significativa en las tasas de incidencia de la enfermedad, se ha establecido una mayor mortalidad en los caprinos infectados con PPRV que en ovinos (23).…”
Section: Discussioncontrasting
confidence: 57%
See 1 more Smart Citation
“…The reported prevalence of PPR in goats at present study was 1.37% and was in opposite with the results higher prevalence reported by Al-Dubaib (26) (13,(19)(20)(21)(22). Aunque puede no haber una variación significativa en las tasas de incidencia de la enfermedad, se ha establecido una mayor mortalidad en los caprinos infectados con PPRV que en ovinos (23).…”
Section: Discussioncontrasting
confidence: 57%
“…Soundararajan et al (18) also showed a higher mortality rate among infected goats than sheep in a large organized farm. However, higher seroprevalence in sheep as compared to goats has been observed in some other studies (13,(19)(20)(21)(22) Although sheep and goats may not vary significantly in qualifications of disease incidence but a higher mortality rate in PPRV infected goats than in sheep has been established (23).…”
Section: Discussionmentioning
confidence: 90%
“…It is widely believed that the spread of PPRVs is closely related to the movement of herds (Balamurugan et al., ; Singh et al., ; Munir et al., ), as is equally plausible in China. In recent years, continued high price of mutton in China led to vigorously developed goats and sheep husbandry.…”
Section: Resultsmentioning
confidence: 99%
“…There was no subdivision among viruses. Munir et al (2013) detected a clear division in 2 groups among sequences of PPR viruses isolated from an outbreak and indicated that the genetic divergence among PPR viruses was slightly higher in the N gene (6.2%) than the F gene (5.2%). The analyses of the N, M, F, and H gene sequences of virulent isolates and vaccine strains of PPR viruses of Indian origin showed considerable sequence homology among lineage IV viruses .…”
Section: Discussionmentioning
confidence: 97%